1999
DOI: 10.1111/1467-9481.00080
|View full text |Cite
|
Sign up to set email alerts
|

On the narrative vs non‐narrative functions of reported speech: A socio‐pragmatic study

Abstract: Reported utterances have often been analyzed with regard to their narrative function. While it is true that this narrative function applies to a large group of cases, we have observed that reported speech can ful®l other functions, which are incompatible with the properties of a narrative utterance. This study, based on spontaneous discourse, will focus on the non-narrative functions of reported speech, that is, the appreciative, the support and the authority functions. We will ®rst de®ne the semantico-pragmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
13
0
4
Order By: Relevance
“…On first glance, this is not surprising when we consider the research on the correlations between the functions of reported speech and age which shows that younger speakers are more likely than older speakers to use reported speech to illustrate a previous comment or idea or to express their own thoughts or opinions (Vincent and Perrin :307). However, what is particularly notable about the uses of reported speech in this study is the similarity in the content and structuring of reported exchanges among younger residents.…”
Section: Discussionmentioning
confidence: 99%
“…On first glance, this is not surprising when we consider the research on the correlations between the functions of reported speech and age which shows that younger speakers are more likely than older speakers to use reported speech to illustrate a previous comment or idea or to express their own thoughts or opinions (Vincent and Perrin :307). However, what is particularly notable about the uses of reported speech in this study is the similarity in the content and structuring of reported exchanges among younger residents.…”
Section: Discussionmentioning
confidence: 99%
“…First, reported speech has often been analyzed as sometimes having authority-and objectivity-enhancing effects in interaction (e.g. Clift 2007, Heritage and Raymond 2005, Vincent and Perrin 1999. I argue that such effects are, however, largely orthogonal to the relationship between speaker and quoted utterance that we are considering here.…”
Section: Cqf and The Pragmatics Of Quotationmentioning
confidence: 91%
“…Niels uses reported speech, with curses in it. This gives an air of authenticity; there is a difference between claiming to be committed to sales and narrating events demonstrating the commitment (Vincent & Perrin 1999).…”
Section: H a B I T U S A S T H E P R I N C I P L E F O R S O C I A L mentioning
confidence: 99%